Gaya Pengasuhan Orang Tua dan Prokrastinasi Akademik Mahasiswa: Tinjauan Literatur - Elly Ermawati; Itsna Iftayani; Patria Jati Kusuma (Jurnal Psikologi Perseptual, 2026)
The high levels of academic procrastination among students today pose a serious challenge to the quality of graduates and the education system, making it crucial to evaluate the role of parenting styles as a determining factor. This procrastination has a negative impact on academic performance and is significantly influenced by parental parenting styles. This literature review aims to explore the relationship between parenting styles and procrastination through an analysis of studies from 2020–2025. Following the PRISMA guidelines, articles were selected from the Scopus, Web of Science, Semantic Scholar, and Google Scholar databases using the Rayyan platform with strict criteria. Eight articles were selected for in-depth analysis. The findings indicate that democratic parenting reduces procrastination through open dialogue, independence, and self-discipline. Conversely, permissive and authoritarian parenting styles trigger increased procrastination due to weak self-control or psychological pressure. These findings provide scientific insights into the specific influence of parenting styles as a foundation for self-regulation interventions among students in the digital age. Parents are advised to adopt a parenting style that balances warmth and responsibility. Further research is needed to examine the effectiveness of modern parenting models, such as digital and mindful parenting, in reducing procrastination. Tingginya prokrastinasi akademik mahasiswa saat ini menjadi tantangan serius bagi kualitas lulusan dan sistem pendidikan, sehingga evaluasi peran pola asuh sebagai faktor penentu sangat penting dilakukan. Penundaan ini berdampak negatif pada prestasi belajar dan dipengaruhi secara signifikan oleh gaya pengasuhan orang tua. Tinjauan literatur ini bertujuan mengeksplorasi hubungan pola asuh dan prokrastinasi melalui analisis studi tahun 2020–2025. Mengikuti pedoman PRISMA, artikel diseleksi melalui basis data Scopus, Web of Science, Semantic Scholar, dan Google Scholar menggunakan platform Rayyan dengan kriteria ketat. Delapan artikel dipilih untuk analisis mendalam. Temuan menunjukkan bahwa pola asuh demokratis mengurangi prokrastinasi melalui dialog terbuka, kemandirian, dan disiplin diri. Sebaliknya, pola asuh permisif dan otoriter memicu peningkatan prokrastinasi akibat lemahnya kontrol diri atau tekanan psikologis. Temuan ini memberikan kontribusi ilmiah mengenai pengaruh spesifik gaya pengasuhan sebagai landasan intervensi regulasi diri mahasiswa di era digital. Orang tua disarankan menerapkan pola asuh yang seimbang antara kehangatan dan tanggung jawab. Peneliti selanjutnya perlu mengkaji efektivitas model pengasuhan modern, seperti digital dan mindful parenting dalam mengurangi prokrastinasi.